CONDITIONS OF THE MECHANICAL SYSTEM MOTION STABILITY LOSS INTERACTING WITH A TRIBOMEDIUM - V.L. ZAKOVOROTNY; A.D. LUKJANOV; V.E. STUPIN (Advanced Engineering Research)
Conditions of the motion stability loss of a mechanical system interacting with a medium that is formed at a tribomating are discussed. Conditions of the formation and the role of dissipative, gyroscopic, potential and circulation forces that are formed at the friction node by the natural way have established.